Housing stock and dwelling conditions in Uniejów - Milewska-Osiecka, Katarzyna; Ogrodowczyk, Agnieszka (Biuletyn Uniejowski, 2014)
The main purpose of the paper is to analyze the size and structure of housing stock located within the borders of Uniejów, as well as studying the existing dwelling conditions. In the first part of the article the authors present a brief historical overview of housing development and contemporary location of residential areas in the examined small town. Analysis of housing conditions, the results of which were presented in the second part of the paper, were based on surveys conducted in 2013, which also allowed to obtain an inhabitants’ opinions on the subject. The collected data and performed analysis of dwelling conditions in Uniejów lead to the conclusion that, in general, they have improved slightly in recent years (this is also a feature of the whole set of small towns in Poland).